Sixty years of the RISM - Kraus, Guido (Katedra Muzykologii, Wydawnictwo Naukowe PTPN, Wydawnictwo Naukowe UAM, 2012)
The individual RISM working groups in Europe and beyond supply a shared transnational electronic database, which all scholars can examine to gain an overview of the state of sources in their area of research. The RISM’s projects, in particular the music manuscript project of series A/II, are far from complete and continue to grow. The author presents not only the project as a whole but also the RISM’s work in Poland in the past, present and future.
Keywords: RISM